Writing that breaks stones African child soldier narratives - Uraizee, Joya F. (Joya Farooq), 1961- (Michigan State University Press, 2020)
"This book argues that the dominant literary mode that characterizes memoirs and novels about African child soldiers is ambiguity. It explores memoirs, such as Keitetsi's Child Soldier; Mehari's Heart of Fire; Beah's A Long Way Gone; Jal's and Davies's War Child; Akallo's and McDonnell's Girl Soldier; and Kamara's and McClelland's A Bite of the Mango, and compares these accounts with novels, such as Kourouma's Allah is Not Obliged; Dongala's Johnny Mad Dog; Iweala's Beasts of No Nation; Jarrett-Macauley's Moses, Citizen, and Me; Adichie's Half of a Yellow Sun; and Abani's Song for Night"--